Peran Supervisi Kepala Sekolah dalam Meningkatkan Kinerja Guru Kelas Jenjang SD pada Gugus XXXVI Ateuk Kecamatan Kuta Baro Kabupaten Aceh Besar - Nufriadi, Nufriadi; Putra, Mulia; Mukhlisuddin, Mukhlisuddin (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the role of principal supervision in improving the performance of elementary school class teachers in cluster XXXVI Ateuk, Kuta Baro District, Aceh Besar Regency. This research uses a qualitative approach with a case study type. Data collection through in-depth interviews and observations. While data analysis techniques include data reduction, data presentation and conclusion making. The results of the study show that the supervision of the principal plays a role in improving teacher performance, improving teacher performance, especially in the learning process. The role of the principal as a supervisor in improving teacher performance is to act as a coordinator, consultant, group leader and evaluator. Supervision activities of school principals in improving teacher performance are carried out through planning, implementation, and evaluation. The implementation of supervision is carried out to see the condition of learning activities carried out by teachers, namely, to check the suitability of learning tools with their application in class, if not this is what is evaluated, and guidance and coaching are carried out to be better.